2020
DOI: 10.3889/oamjms.2020.4298
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Alpha Glucosidase Activity of Uncaria gambir Roxb. and Syzygium polyanthum (Wight) Walp. from West Sumatra, Indonesia

Abstract: BACKGROUND: Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormal insulin secretion, insulin action, or both. Alpha-glucosidase enzyme inhibitors are drugs that work by slowing the absorption of carbohydrates in the intestine so that it has an impact on decreasing post-prandial glucose levels. AIM: The aim of the study was to assess the alpha-glucosidase inhibitory activities of methanolic extracts from different parts of Uncaria gambir Roxb. and Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Previous in vitro studies have shown that quercetin, catechin, curcumin and 6-gingerol actively inhibit αglucosidase at the IC50 values are 65.52 µg/mL (Limanto et al, 2019), 30.85 µg/mL (Arundita et al, 2020), 6. 9 µg/mL (Lekshmi et al, 2014) and 21.55 µg/mL (Mohammed et al, 2017).…”
Section: Resultsmentioning
confidence: 96%
“…Previous in vitro studies have shown that quercetin, catechin, curcumin and 6-gingerol actively inhibit αglucosidase at the IC50 values are 65.52 µg/mL (Limanto et al, 2019), 30.85 µg/mL (Arundita et al, 2020), 6. 9 µg/mL (Lekshmi et al, 2014) and 21.55 µg/mL (Mohammed et al, 2017).…”
Section: Resultsmentioning
confidence: 96%